Improved design of control segment in BDS‐3. Issue 1 (25th March 2019) - Liu, Li; Zhang, Tianqiao; Zhou, Shanshi; Hu, Xiaogong; Liu, Xiaoping
Abstract: The Chinese BeiDou Navigation Satellite System (BDS) is accelerating its development and has been applied in various fields. Compared with other satellite navigation systems in the world, BDS has many unique features such as multiservices integrated with Radio Determination Satellite Service (RDSS), Radio Navigation Satellite Service (RNSS), and Satellite‐Based Augmentation Service (SBAS), a mixed‐orbit satellite constellation, and flexible navigation messages, etc. This paper presents the distinctive innovative designs as well as processing strategies in BDS. First, this paper introduces the characteristics of BeiDou navigation messages broadcast by the hybrid constellation of satellites in Geostationary Earth Orbit (GEO), Inclined Geo‐Synchronization Orbit (IGSO), and Medium Earth Orbit (MEO). Next, the innovative design and operation of the control segment are discussed. Finally, highlights of the unique usage algorithm of the BDS navigation message information are presented, such as the BDS satellite clock correction and TGD parameters, satellite ephemeris and almanac, and ionospheric delay parameters.